The fall and rise of Keynesian economics - Eatwell, John.; Milgate, Murray (New York : Oxford University Press, 2011)
During the 1970s, monetarism and the new classical macroeconomics ushered in an era of neoliberal economic policymaking. Keynesian economics was pushed aside. It was almost forgotten that when Keynesian thinking had dominated economic policymaking in the middle decades of the twentieth century, it had coincided with postwar economic reconstruction in both Europe and Japan, and the unprecedented prosperity and stable growth of the 1950s and 1960s. The global financial crisis of 2007-2009 and the recession that followed changed all that. Influential voices in both academic economics and amongst policy-makers and commentators began to remind us how useful Keynesian ways of thinking could be, especially in coming to terms with our current economic predicaments. When politicians across the globe were confronted with economic crisis, they introduced pragmatic and workable measures that bore all the hallmarks of Keynesianism. This book is about the fall and rise of Keynesian economics. Eatwell and Milgate range widely across the landscape that defines their subject matter. They consider how powerful Keynesian ideas can be when applied to past and present economic problems. They show how helpful these ideas are in explaining why we came to find ourselves in the disorder we are in. They examine where and how the analytical and methodological foundations of conventional macroeconomic wisdom went wrong. They set out a blueprint for an alternative that provides a clearer, more consistent, and more applicable approach to understanding how markets work. They also highlight the interpretive shortcomings that have come to characterize Keynes scholarship itself. They do all of this within the context of a provocative reconsideration of some of the most pressing economic problems that confront financial markets and the global economy today. They conclude that Keynesian ideas are not just for crises, but for constructive economic policy making at all times. -- Product Description.
The fall & rise of Keynesian economics -- Practical -- Liquidity and financial crises -- A practical approach to the regulation of risk -- Can Barack Obama do it? -- Useful bubbles -- Unemployment on a world scale -- International financial liberalisation -- Analytical -- The imperfectionists -- Effective demand and disguised unemployment -- Theories of value, output and employment -- Money, capital & forced saving -- Critical -- Unemployment & the market mechanism -- The analytical foundations of monetarism -- Controversies in the theory of employment -- Is the International Monetary Fund past its sell-by date? -- Historical -- Keynes's general theory -- Keynesian economic theory & European society -- The gold standard & monetary theory -- The economic possibilities of capitalism.
Includes bibliographical references and index.
Description based on online resource; title from pdf title page (EBSCO, viewed on December 13, 2021).
eBooks on EBSCOhost
Keywords: Keynesian economics; Economic history -- 1918-1945.; Economic history -- 1945-; Keynésianisme.; Histoire économique -- 1918-1945.; Histoire économique -- 1945-; BUSINESS & ECONOMICS -- Economics -- Theory; Economic history; Keynesian economics; Since 1918